Christopher Columbus and Neil Armstrong - Hunter, Nick (Chicago, Illinois Heinemann Raintree, an imprint of Capstone Global Library, 2015)
How did the journeys of Christopher Columbus and Neil Armstrong compare? Follow both of these daring adventurers into history to discover the differences and similarities between their amazing expeditions! Addressing the needs of the Common Core, this book will encourage children to compare and contrast two very special lives
A gift from book Africa
Famous People
1 2 13 15
Keywords: Armstrong, Neil -- 1930-2012; Armstrong, Neil -- 1930-2012 -- Juvenile literature; Columbus, Christopher -- Juvenile literature